2015
DOI: 10.1097/sap.0000000000000408
|View full text |Cite
|
Sign up to set email alerts
|

Intrathoracic Migration of a Breast Implant After Minimally Invasive Cardiac Surgery

Abstract: The aging population, in combination with the popularity of breast augmentation with implants, presents surgeons with a growing number of cases involving women undergoing minimally invasive cardiac surgery (MICS) who have breast implants. We present an unusual complication involving the delayed migration of a subpectoral implant into the chest cavity through an iatrogenic defect after a minimally invasive mitral valve repair. This chest wall defect was ultimately repaired with a latissimus dorsi flap. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…12 However, intraoperative manipulation of the implant has been associated with several complications such as implant leakage, breast deformity, and secondary implant migration. 9,13, 14 Pervaiz et al reported a successful MIMVS after breast augmentation without explanting the prosthesis. 11 Also, Je et al reported a successful minimal-invasive combined atrium septum defect closure and tricuspid valve reconstruction with capsule preservation of a breast implant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 However, intraoperative manipulation of the implant has been associated with several complications such as implant leakage, breast deformity, and secondary implant migration. 9,13, 14 Pervaiz et al reported a successful MIMVS after breast augmentation without explanting the prosthesis. 11 Also, Je et al reported a successful minimal-invasive combined atrium septum defect closure and tricuspid valve reconstruction with capsule preservation of a breast implant.…”
Section: Discussionmentioning
confidence: 99%
“… 12 However, intraoperative manipulation of the implant has been associated with several complications such as implant leakage, breast deformity, and secondary implant migration. 9 13 14 …”
Section: Discussionmentioning
confidence: 99%
“…12 However, intraoperative manipulation of the implant has been associated with several complications such as implant leakage, breast deformity, and secondary implant migration. 9,13 14 Pervaiz et al reported a successful MIMVS after breast augmentation without explanting the prosthesis. 11 Also, Je et al reported a successful minimal-invasive combined atrium septum defect closure and tricuspid valve reconstruction with capsule preservation of a breast implant.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Currently, few reports in the literature detail the optimal approach to managing women with prior breast implants who present for cardiothoracic (CT) interventions. Case series have been described, highlighting the concern for unintentional breast implant manipulation during CT surgery 4,5 . However, findings are limited to small patient cohorts, heterogeneity between patients and surgical interventions, and lack of statistical power to formulate conclusions about defining optimal clinical practice.…”
mentioning
confidence: 99%
“…Case series have been described, highlighting the concern for unintentional breast implant manipulation during CT surgery. 4,5 However, findings are limited to small patient cohorts, heterogeneity between patients and surgical interventions, and lack of statistical power to formulate conclusions about defining optimal clinical practice. There remains a need to determine the safety and complication rates of patients with breast implants who undergo CT interventions.…”
mentioning
confidence: 99%